PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK TALK WRITE TERHADAP HASIL BELAJAR PPKN PADA SISWA KELAS V UPT SPF SD INPRES BONTOMANAI KOTA MAKASSAR - Ilmayanti, Andi Resky; Nur, Jumiati; Hakim, Ulfayani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the cooperative learning model Think Talk Write on the learning outcomes of fifth-grade students in Pancasila Education (PPKn) at UPT SPF SD Inpres Bontomanai, Makassar City, using a quantitative approach with a quasi-experimental design (Nonequivalent Control Group Design). The sample consisted of 48 students, including 21 students in the experimental class and 27 students in the control class. Data were collected through tests, observations, and documentation, and analyzed using descriptive and inferential statistics. The results showed an improvement in learning outcomes in both groups, with a more significant increase in the experimental class (mean score from 70.00 to 88.00; mastery from 48% to 100%) compared to the control class (58.00 to 75.00; mastery from 11% to 37%), and the implementation of the model was categorized as high (86%). Hypothesis testing revealed a significance value of 0.002 (< 0.05) and a t-value of 3.338 > 2.012, indicating that the Think Talk Write model has a positive and significant effect on learning outcomes, while also enhancing students’ understanding and active participation in the learning process.